Histological evaluation of human amniotic membrane graft on oral keratinizing mucosa in the rabbit model (A pilot study) - Samandari Najafabadi MH; Shahrabi Farahani Sh; Kheirollahi H (Tehran University of Medical Sciences, 2007)
Background and Aim: One of the complications following major oral surgeries is mucosal defects and delayed healing process. Up to now, various mucocutaneous grafts have been used in this field and recently, amniotic membrane has been proposed as a biological dressing in dermatologic, ophthalmologic and otolaryngologic practices. The purpose of this pilot study was to evaluate the healing process following human amniotic membrane graft on oral keratinized mucosa of rabbit.Materials and Methods: In this experimental animal study, two surgical mucosal defects with the same size were made in palatal mucosa of 10 rabbits with the same weight, gender and race and a graft of human amniotic membrane was used on one of the defects. On the 7th, 14th and 28th postoperative days, surgical biopsies were randomly obtained from grafted and ungrafted regions of 3, 4 and 3 rabbits, respectively and submitted for microscopic study. Results: According to the results, grafted regions showed more surface epithelialization and thicker newly formed epithelium. Also inflammatory cells infiltration was less in these areas. In all cases, there was a remarkable cartilage formation in the connective tissue of the recipient sites.Conclusion: The results of this study suggest that the use of amniotic membrane graft in oral surgery could be effective in healing process. Additional studies should be done using animal and human models with more samples. Furthermore, the formation of cartilage in the grafted sites and its possible potential in reconstruction of bone defects, needs to be studied.